Species and Carbon Sequestration of Vascular Plants in Ban Nang Tho Seasonal Flooding Forest, Mueang Yang District, Nakhon Ratchasima Province - Choopan, Thiamhathai (Srinakharinwirot University Journal of Sciences and Technology, 2025)
Seasonal flooding forest are riparian forests that are continuously declining due to a lack of understanding about conservation and utilization among communities and relevant agencies. This research aims to study plant species and carbon sequestration efficiency in the community forest of Ban Nang Tho, Muang Yang District, Nakhon Ratchasima Province, which is one of the few remaining floodplain forest along the Mun River in the province. A survey of vascular plants in an area of 80 rai (approximately 32 acres) revealed 45 families, 113 genera, and 138 species of plants. The plant diversity index value was 3.66. The evenness value was 0.74. The family with the highest number of species was Fabaceae with 24 species, followed by Rubiaceae with 11 species, Phyllanthaceae with 7 species, and Anacardiaceae, Capparaceae, Euphorbiaceae, and Sapindaceae with 5 species each. The dominant plant species in the area included Streblus asper Lour., Sindora siamensis Teijsm. ex Miq., Dalbergia nigrescens Kurz, Diospyros rhodocalyx Kurz, Olax scandens Roxb., Schoutenia ovata Korth., Lagerstroemia floribunda Jack, Microcos tomentosa Sm., Combretum quadrangulare Kurz, and Brachypterum scandens (Roxb.) Wight & Arn. ex Miq., listed in order of their abundance. The top 5 plant species with the highest above-ground biomass, carbon storage, and carbon dioxide absorption were Dalbergia nigrescens Kurz, Pterocarpus macrocarpus Kurz, Streblus asper Lour., Sindora siamensis Teijsm. ex Miq., Diospyros rhodocalyx Kurz. Their above-ground biomass amounts were 30.66, 30.23, 17.33, 15.91, and 15.14 tons, respectively. Carbon storage amounts were 15.33, 15.11, 8.67, 7.96, and 7.57 tons of carbon, respectively. And carbon dioxide absorption amounts were 56.26, 55.47, 31.81, 29.20, and 27.79 tons of carbon dioxide, respectively.